The Use Of Online Learning Platform And Inhibiting Factors During The Covid-19 Pandemic Students Department Of Pancasila And Civic Education Class 2020 At PGRI Wiranegara University, Pasuruan City - Ayu Maya Damayanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of this study was to find out the learning platform, as well as the inhibiting factors for the online learning process during the Covid-19 period, students of the Pancasila and Citizenship Education study program class of 2020 at PGRI Wiranegara University, Pasuruan City. This research is a survey research or field study with a qualitative method. Data collection techniques used are interview techniques and questionnaires. Based on the data obtained several learning platforms used during online learning, including: zoom, google meet, google class room, whatApps group, telegram group, LMS (moddle). From the results of data analysis, it was found that the most dominant learning platform used was LMS Mddle. In addition, the respondent's results on the inhibiting factors found several factors, including: 1) limited internet quota; 2) unstable network; 3) difficulty understanding the material delivered from online lecturers; 4) cellphone/laptop facilities